Small hydropower impacts on water quality: A comparative analysis of different assessment methods - Paweł Tomczyk; Michał Tymcio; Alban Kuriqi; José Maria Santos; Mirosław Wiatkowski (Water Resources and Industry, 2025)
This study aims to evaluate the spatial and temporal variations of physico-chemical parameters at selected small run-of-river hydropower plants along a 126 km section of the Bóbr River in southwestern Poland. The main contribution of this study lies in comparing different water quality classification methods from different regions worldwide. Our results show that the spatio-temporal changes in physico-chemical parameters in the studied section of the Bóbr River are, to a larger extent, due to anthropogenic pressures (i.e., urbanization and agriculture) unrelated to the operation of hydropower plants. Analysis of variance (ANOVA) confirmed the statistical significance (p < 0.05) of the results for 8 (i.e., EC, temperature, pH, DO, NO2-N, TDS, NH4-N, and COD) out of 16 physicochemical parameters. Hierarchical cluster analysis also showed a greater influence of factors other than hydropower plants on water quality. The average compliance with the standards based on the selected water quality classifications was 76.9%. The Polish classification proved to be the most appropriate classification for assessing the status of physico-chemical elements of the Bóbr River. The findings from this study can be used for various applications, e.g., formulating strategies for sustainable water management in hydropower plant catchment areas, planning new hydropower plants, and developing operating regulations for existing plants.